Morbimortalidade por causas externas em um centro de trauma no município de Campina Grande, Paraíba - Lucena, Belchior de Medeiros (2012)
Objective: To analyze the morbidity and mortality from external causes in patients treated at the Regional Hospital of Emergency and Trauma in Campina Grande, PB. Methodology: This was a cross-sectional descriptive and analytical study using secondary data. We analyzed medical records of 9,734 patients treated at between January 2009 and December 2009, being selected in 1889(19,4%) confirmed cases of patients affected by external causes that were distributed according to etiology. The data collection tool was formulated according to the information in medical records. The ethical aspects of research with human subjects were met: the project was approved by the ethical committee for research of UEPB and also was authorized by the direction of the institution. In the data analysis were used techniques of descriptive statistics (absolute and percentage distributions) and inferential (chi-squared or Fisher's exact test, likelihood test, confidence intervals and odds ratio), adopting a significance level of 5,0%, with confidence intervals of 95.0%. The statistical program used to prepare the database and make the statistical calculations was SPSS (Statistical Package for Social Sciences) version 15. Results: The age of patients ranged from 0 to 99 years, had a mean of 30.74 years, median 27.00 years and standard deviation of 19.80 years. Of the 1789 surveyed, 1376 (76.9%) were male and 413 (23.1%) were female. The higher frequency of cases occurred on Sunday (18.6%) and the others days corresponded to percentages ranging from 11.6% to 15.4%. The category of 18:01 to 24:00 h showed the highest frequency of cases (37.9%). The most frequent etiologies were motorcycle accident (20.8%), falls (19.8%), burns (11.2%), gunshots(10.5%), snake bite (8.5%) and stab wound (8.3%). The body regions most affected were the lower limbs (36.2%), upper limbs (32.4%), chest (16.8%), abdomen (14.2%) and face (12.0%). A significant association was observed between violence and the age of the second, third and fourth decades of life and among those surveyed were male (24.4% vs 6.5%). Conclusions: The subjects were male, young, in the age of the second, third and fourth decades of life are more susceptible to external causes and particularly violence and traffic accidents. Vascular lesions are uncommon and are associated with longer hospitalization and higher mortality.